Effects of the czech propolis on sperm mitochondrial function - Cedikova, Miroslava; Miklikova, Michaela; Stachova, Lenka; Grundmanova, Martina; Tuma, Zdenek; Vetvicka, Vaclav; Zech, Nicolas; Kralickova, Milena; Kuncova, Jitka (Evidence-based complementary and alternative medicine, 2014)
Propolis is a natural product that honeybees collect from various plants. It is known for its beneficial pharmacological effects. The aim of our study was to evaluate the impact of propolis on human sperm motility, mitochondrial respiratory activity, and membrane potential. Semen samples from 10 normozoospermic donors were processed according to the World Health Organization criteria. Propolis effects on the sperm motility and mitochondrial activity parameters were tested in the fresh ejaculate and purified spermatozoa. Propolis preserved progressive motility of spermatozoa in the native semen samples. Oxygen consumption determined in purified permeabilized spermatozoa by high-resolution respirometry in the presence of adenosine diphosphate and substrates of complex I and complex II (state OXPHOSI+II) was significantly increased in the propolis-treated samples. Propolis also increased uncoupled respiration in the presence of rotenone (state ETSII) and complex IV activity, but it did not influence state LEAK induced by oligomycin. Mitochondrial membrane potential was not affected by propolis. This study demonstrates that propolis maintains sperm motility in the native ejaculates and increases activities of mitochondrial respiratory complexes II and IV without affecting mitochondrial membrane potential. The data suggest that propolis improves the total mitochondrial respiratory efficiency in the human spermatozoa in vitro thereby having potential to improve sperm motility.